2018
DOI: 10.1002/slct.201802003
|View full text |Cite
|
Sign up to set email alerts
|

DFT, QTAIM and NBO Investigation of the Interaction of Rare Gases with Pristine and Decorated Boron Nitride Nanotube

Abstract: In this work, the interactions of pristine, Al‐ and Ga‐doped single walled armchair (5,5) boron nitride nanotubes (BNNTs) with He, Ne, Ar and Kr rare gases (RGs) were fully investigated using several different density functional theory (DFT) functionals including pure‐GGA (PBEPBE), hybrid‐GGA (B3LYP), meta‐hybrid‐GGA (M062X) and long‐range‐corrected B3LYP (CAM−B3LYP) in combination with two 6–31G(d) and 6–311+G(d) basis sets. Natural bond orbital (NBO) and quantum theory of atoms in molecule (QTAIM) analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…According to this table, the predicted trend of the adsorption energies of the noble gases onto nanotubes in both calculations is similar and is as follows: Ne &γτ“; Kr > Ar > He. This trend is in fair agreement with the available results in the literature,, and reveals that the adsorption energies are not related to the size of the noble gases. Furthermore, the obtained adsorption energies of AlN(Ga)NT and SiC(Ge)NT are more negative than those of the pristine AlNNT and SiCNT, which implies that, the Ga and Ge dopants can significantly activate the outer surface of the AlN and SiC nanotubes in order to better sensing of the noble gases.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…According to this table, the predicted trend of the adsorption energies of the noble gases onto nanotubes in both calculations is similar and is as follows: Ne &γτ“; Kr > Ar > He. This trend is in fair agreement with the available results in the literature,, and reveals that the adsorption energies are not related to the size of the noble gases. Furthermore, the obtained adsorption energies of AlN(Ga)NT and SiC(Ge)NT are more negative than those of the pristine AlNNT and SiCNT, which implies that, the Ga and Ge dopants can significantly activate the outer surface of the AlN and SiC nanotubes in order to better sensing of the noble gases.…”
Section: Resultssupporting
confidence: 91%
“…The strength of the interactions may be estimated using the topological QTAIM analysis of the BCP. Accordingly, following our previous works,, , some conceptual parameters of topological QTAIM analysis, including electron density, ρ (r), the Laplacian of the electron density, V 2 ρ (r), the ratio of kinetic electron energy ( G (r)) to the absolute value of the potential electron energy density (| V (r)|), the bond ellipticity ( ϵ ) and the eigenvalues of Hessian matrix ( λ x ) were calculated at the attained BCPs, and the obtained results were reported in Table . BCPs for the adsorption of Ne gas onto the outer surface of SiC, SiC(Ge), AlN, and AlN(Ga) nanotubes have also been represented graphically in Figure .…”
Section: Qtaim and Nbo Analysesmentioning
confidence: 99%
“…Also, values of 1(r) > 0 and correspond to the close-shell bonds (i. e. noncovalent vdW and ionic interactions). [46,47] The nature of the interaction can also be derived from the ratio of G(r) (i. e. electron kinetic energy density) to V(r) (i. e. electron potential energy density). For 0 < G(r)/ j V(r) j < 0.5 the interaction is covalent, and for 0.5 < G(r)/ j V(r) j < 1 the bond is a mixed covalent-ionic.…”
Section: Qtaim and Nbo Analysesmentioning
confidence: 99%
“…Meanwhile, theoretical studies on nanoscale structures have found an extraordinary place in computational chemistry, and researchers have used numerous computational methods to study intermolecular interactions to design tools that have better accuracy and performance [1][2][3][4][5]. A variety of nanomaterials have been considered for the construction of sensors with high measurement accuracy, extreme insensitivity to temperature, very low response time, low production costs, and resistant to harsh environmental conditions [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%